Growth of celery (Apium graveolens L.) in the red-yellow podzolic soils as inoculated by earthworms Pontoscolex corethrurus - Seprita Lidar; Indra Purnama (Universitas Lancang Kuning, 2021)
In this study, the inoculation effect of earthworms Pontoscolex corethrurus on celery growth (Apium graveolens L.) has been carried out in red-yellow podzolic (RYP) soils. The research studied in a pot experiment using a completely randomized design (CRD) with 6 (six) treatments and 3 (three) replications. One-pot consists of 4 (four) plants. The treatments carried out were as follows: I0 (without inoculum of earthworm), I1 (inoculum of 5 earthworms pot-1), I2 (inoculum of 10 earthworms pot-1), I3 (inoculum of 15 earthworms pot-1), I4 (inoculum of 10 earthworms pot-1) and I5 (inoculum of 25 earthworms pot-1). Observation parameters were the number of tillers clumps-1, fresh biomass clumps-1 (g clump-1), and root volume (mL). The observations were statistically analyzed using variance (one-way ANOVA) and followed by the Duncan Multiple Range Test (DMRT) with a level of 5%. Treatment I5 gave the best results on celery crop in all parameters, i.e., 20.33 tillers per hill; fresh biomass per clump 113.93 g; and a root volume of 10 mL. The results showed that earthworms' inoculation into RYP soils significantly affected all parameters. There was also an increase in pH in each treatment that was inoculated with earthworms.